Swim-training volume and shoulder pain across the life span of the competitive swimmer: A systematic review - Feijen, S.; Tate, A.; Kuppens, K.; Claes, A.; Struyf, F. (Journal of Athletic Training, 2020)
Background: Competitive swimmers are exposed to enormous volumes of swim training that may overload the soft tissue structures and contribute to shoulder pain. An understanding of training factors associated with the injury is needed before practice guidelines can be developed.